(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The present study was carried out to estimate phenotypic and genetic parameters of Red Chittagong Cattle (RCC) for growth traits. Means of birth weight (BW), three month weight (3MW), six month weight (6MW), weaning weight (WW), nine month weight (9MW) and yearling weight (YW) were 15.74, 31.48, 45.33, 57.00, 60.91 and 76.18 kg respectively. Sex significantly (p<0.001) differed BW of calves but did not differ (p>0.05) 3MW, 6MW, WW, 9MW and YW. BW, 6MW, WW, 9MW and YW did not vary significantly (p>0.05) on year of birth but varied significantly (p<0.01) on 3MW. Season of birth had significant difference on 3MW (p<0.001), 6MW (p<0.01) and WW (p<0.01) but had no significant difference (p>0.05) on BW, 9MW and YW. The growth rates at zero to six month (6MGR) and six to twelve month (12MGR) were 0.17 and 0.17 kg /d respectively. Growth rate in both stages had no significant effect (p>0.05) on sex and year of birth. 6MGR had no significant effect (p>0.05) on season of birth but had significant (p<0.05) effect on 12MGR. From single trait analyses heritability (h2) of BW, 3MW, 6MW, WW, 9MW, YW, 6MGR and 12MGR were 0.497, 0.468, 0.475, 0.467, 0.447, 0.478, 0.499 and 0.65, respectively, whereas from multi-trait analysis heritability (h2) of first four traits were 0.498, 0.456, 0.500 and 0.490, respectively. Genetic correlations of BW with 3MW, 6MW and WW were 0.23, 0.38, and 0.53, respectively, 3MW with 6MW and WW were 0.78 and 0.69, respectively and 6MW with WW was 0.76. Estimated heritability values were rather high in magnitude and indicate that these traits would likely respond to selection. Estimates of phenotypic correlations among the traits studied were very low to moderate with values ranging from -0.40 to 0.81, whereas magnitude of genetic correlation ranged from 0.23 to 0.78. It was concluded that these estimated parameters would help to understand the biology of the traits and in designing breeding programme for other indigenous cattle in general. Keywords: Phenotypic and Genetic parameters; Growth traits; Red Chittagong cattle DOI: 10.3329/jbau.v7i2.4733 J. Bangladesh Agril. Univ. 7(2): 265-271, 2009